PENDIDIKAN MORAL DI TENGAH KRISIS ETIKA GENERASI MUDA - Andika Pratama; Zidni Ilman NZ (TANZHIMUNA : Jurnal Manajemen Pendidikan Islam, 2025)
This study examines the implementation of moral education in addressing the ethical crisis among the younger generation, particularly students at MTS Nurul Huda Banjar Agung Mataram. The ethical crisis, characterized by a decline in moral values, manners, and positive character among the younger generation, poses a serious challenge in the world of education. This study uses a qualitative approach with a case study method to analyze the moral education strategies implemented in the madrasah. Data were collected through observation and in-depth interviews with teachers and the principal. The results show that moral education at MTS Nurul Huda Banjar Agung Mataram is implemented through the integration of Islamic values in learning, the cultivation of noble character, teacher role modeling, and character-based extracurricular programs. However, there are still various obstacles, such as the influence of social media, peer groups, and minimal parental involvement. This study recommends the need for synergy between schools, families, and communities in strengthening moral education for the younger generation.